2020
DOI: 10.1186/s12917-020-02542-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic profiling of myxomatous mitral valve disease in the cavalier King Charles spaniel

Abstract: Background Almost all elderly dogs develop myxomatous mitral valve disease by the end of their life, but the cavalier King Charles spaniel (CKCS) has a heightened susceptibility, frequently resulting in death at a young age and suggesting that there is a genetic component to the condition in this breed. Transcriptional profiling can reveal the impact of genetic variation through differences in gene expression levels. The aim of this study was to determine whether expression patterns were differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…This study showed that despite the 100% prevalence of MMVD in this population of aged CKCSs, a relatively large proportion (44%) showed an absence of cardiac remodelling, indicating that a proportion of elderly CKCSs with confirmed MMVD do not undergo advanced stages of this pathology. This could be because the form of MMVD affecting CKCS at a young age, for which strong heritability has been demonstrated [42], is more aggressive and leads to death in young subjects, while a sub-cohort of dogs are affected by milder disease, more similar to that affecting all elderly dogs regardless of breed [43], which allows them to live longer. Identification of genetic and pathophysiologic mechanisms that lead to delayed progression of the disease may warrant future studies in order to reduce the clinical impact of the condition in this breed.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that despite the 100% prevalence of MMVD in this population of aged CKCSs, a relatively large proportion (44%) showed an absence of cardiac remodelling, indicating that a proportion of elderly CKCSs with confirmed MMVD do not undergo advanced stages of this pathology. This could be because the form of MMVD affecting CKCS at a young age, for which strong heritability has been demonstrated [42], is more aggressive and leads to death in young subjects, while a sub-cohort of dogs are affected by milder disease, more similar to that affecting all elderly dogs regardless of breed [43], which allows them to live longer. Identification of genetic and pathophysiologic mechanisms that lead to delayed progression of the disease may warrant future studies in order to reduce the clinical impact of the condition in this breed.…”
Section: Discussionmentioning
confidence: 99%
“…Array genotypes within 500 kb of candidate risk variants identified by Axelsson et al [ 10 ] ( Table 1 and Table 2 ) were extracted from the genome-wide array genotypes using PLINK [ 19 ]. Minor allele frequencies for individual variants (--freq) and genotype counts (--freqx) were reported, with no quality filtering.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, this study found that the genotype for one of the NEBL risk variants ( NEBL3 ) was a significant predictor of graded MMVD disease status in the dachshund. Considering the previous finding of the gene expression differences in NEBL in the CKCS [ 10 ], this is concerning for the breed. If NEBL risk alleles are fixed in the CKCS breed and proven as causative for MMVD risk and/or severity, cross-breeding would be required to breed out severe MMVD in the CKCS.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations